PENGEMBANGAN SISTEM INFORMASI PENGELOLAAN PERALATAN BENGKEL BERBASIS WEB DI SEKOLAH MENENGAH KEJURUAN - Siti Rokhmah; Hasanah Nur; Anas Arfandi (SEMINAR NASIONAL DIES NATALIS 62, 2023)
Information System management of workshop equipment as part of the school plays an important role in handling all equipment inventory and smooth activities in the school workshop carried out by students or teachers in carrying out practices, so an effective data storage place is needed. The problem found related to the processing of inventory data for workshop equipment management at SMKN 2 Makassar is a process that is still carried out manually, so it canpotentially be difficult to detect the existence of inventory data due to changes in workshop managers With the existence of a web-based workshop equipment management information system can help teachersin processing, processing and storing equipment inventory data and providing smoothness in all activities in the school workshop.and also easy access for those who need data and information related to the use of equipment in the school workshop. The development of this system uses a 4D model with 4 main stages, namely: (1) Definie, (2) Design, (3) Develop, and (4) Dessiminate. Expert validation tests were conducted by 2 lecturers to determine the validity of the software/program aspect and obtained an average of 4.9 by meeting the valid criteria. The next test is on practical and effective aspects which was carried out involving 20 respondents and obtained an average practical aspect of 96% and an average effective aspect of 95% so that it is categorized as very practical and effective